2014
DOI: 10.1161/strokeaha.113.004016
|View full text |Cite
|
Sign up to set email alerts
|

Thrombelastography Detects the Anticoagulant Effect of Rivaroxaban in Patients With Stroke

Abstract: Background and Purpose: Factor Xa inhibitors (fXaI) are prescribed for stroke prevention in atrial fibrillation. Managing such patients is challenging especially if they are eligible for thrombolysis, as there is no rapidly available test to detect the effect of such medications. Thrombelastography (TEG) ™ analyzes the dynamics of coagulation and can be rapidly performed. We sought to determine whether TEG™ can detect the anticoagulation effect of fXaI in stroke patients. Methods: Blood from 10 stroke patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 6 publications
1
24
0
Order By: Relevance
“…These settings include cardiac surgery [6770], liver transplantations [71], sepsis [72], trauma [7379], obstetrics [80], psychophysiological stress [81]. These systems have also been utilized to evaluate anticoagulant activity [82, 83] and determine what the critical threshold value is for the initiation of antifibrinolytic therapy in trauma [84]. The platelet mapping assay system, used to measure platelet aggregation, is more frequently being used in the clinical setting [85], including in patients undergoing cardiac surgery and cardiopulmonary bypass, in which their TEG findings as measured using collagen were correlated with postoperative bleeding [86].…”
Section: Thrombin Generation Assaysmentioning
confidence: 99%
“…These settings include cardiac surgery [6770], liver transplantations [71], sepsis [72], trauma [7379], obstetrics [80], psychophysiological stress [81]. These systems have also been utilized to evaluate anticoagulant activity [82, 83] and determine what the critical threshold value is for the initiation of antifibrinolytic therapy in trauma [84]. The platelet mapping assay system, used to measure platelet aggregation, is more frequently being used in the clinical setting [85], including in patients undergoing cardiac surgery and cardiopulmonary bypass, in which their TEG findings as measured using collagen were correlated with postoperative bleeding [86].…”
Section: Thrombin Generation Assaysmentioning
confidence: 99%
“…TEG, an ex vivo technique that measures thrombodynamic properties of blood under low–shear conditions, has been approved by the FDA for diagnosis and management of coagulation disorders. It is also used during surgery . In contrast, HAS is an ex vivo technique that elucidates forces generated by platelets within a clot .…”
Section: Resultsmentioning
confidence: 99%
“…TEG and HAS assays were performed as reported in the literature . For both studies, CaCl 2 was used to initiate clotting of citrated human blood containing varying levels of SCI or enoxaparin.…”
Section: Methodsmentioning
confidence: 99%
“…) and another study found a significant change in TEG parameters in 10 people receiving RIV compared to their baseline values (Bowry et al . ). Power calculation to determine sample size was not performed.…”
Section: Methodsmentioning
confidence: 97%
“…) which is contrary to humans receiving therapeutic levels of RIV where increased R and K values and significantly decreased G, maximum amplitude, alpha angle and LY30 compared to baseline have been reported (Bowry et al . ).…”
Section: Introductionmentioning
confidence: 97%